Journal of Paleolithic Archaeology - Bicho, Nuno.; McPherron, Shannon J. P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Journal of Paleolithic Archaeology is aimed at all Plio-Pleistocene archaeologists and other scientists researching Paleolithic archaeology. It covers all aspects of Paleoanthropology, including biological and cultural human evolution, paleoecology, dating, site formation processes, diet, paleoclimate, taphonomy, zooarchaeology, geoarchaeology and many more fields applied to Paleolithic period sites. JPA publishes archaeological research from the earliest paleoanthropological discoveries in Africa to the peopling of Oceania and the Americas. The Journal publishes four types of studies: Articles, Discussions, Reports, and Short communications and News. All studies should provide new data and discussion on discoveries of sites or hominin fossils; theoretical and methodological advancements; site stratigraphies or other data-descriptive reports including analyses of new or old artefactual collections; and main research studies on Paleolithic archeology addressing broad topics of interest in Paleoanthropology. This journal provides an international environment for archaeologists and other scientists with a wide spectrum of expertise focusing on the development of Plio-Pleistocene archaeology around the world to develop new perspectives and data on human biological and cultural evolution.
Keywords: Archaeology; Archaeology